Ethical Leadership, Transparent Decision-Making, and Organizational Trust : The Mediation Role of Communication Openness in Electronic Companies Bekasi - Apriyanih, Cindy; Putri, Diah Ayu Syahrani (Talent: Journal of Economics and Business, 2025)
This study examines the influence of Ethical Leadership and Transparent Decision-Making Processes on Organizational Trust, with Communication Openness as a mediating variable, in electronics companies in the Bekasi Regency industrial area. In the competitive era of globalization, Organizational Trust is a key element of corporate success. This research is based on the phenomenon of low employee trust in companies, even though the electronics sector shows high potential in the economy. Data was collected through questionnaires distributed to 198 employees who had worked for at least one year. Data analysis was carried out using the Partial Least Squares (PLS) method using SmartPLS. The results of the study show that Ethical Leadership has a significant positive effect on Organizational Trust. Ethical leaders are able to create a work environment that supports trust, especially among young employees with high levels of education. In addition, Transparent Decision-Making Processes have also been shown to contribute positively to Organizational Trust, with transparency in decision-making increasing procedural fairness and two-way communication. Communication Openness functions as a mediator that strengthens the relationship between the two independent variables and Organizational Trust . This research provides important insights for leaders and policy makers in the electronics sector to increase organizational trust, which in turn can drive innovation and productivity. These findings also enrich the literature on the dynamics of ethical leadership and transparency in a corporate context, and emphasize the importance of open communication in building trust in a dynamic work environment.